Dscam2 affects visual perception in Drosophila melanogaster - Bosch, Danny S.; van Swinderen, Bruno; Millard, S. Sean (Frontiers in Behavioral Neuroscience, 2015)
Dscam2, a cell surface protein that mediates cellular repulsion, plays a crucial role in the development of the Drosophila melanogaster visual system. Dscam2 generates boundaries between neighboring modules in the fly optic lobe; in Dscam2 mutants this visual system modularity is compromised. Although developmental wiring defects have been well described in the Dscam2 mutant, behavioral consequences have not been investigated. To address this, we examined the visual behavior of Dscam2 mutant flies. Using a phototaxis assay, we ascertained that these flies are not blind, but have a reduced phototaxic response. Through population-based and single fly optomotor assays, we found that Dscam2 mutant flies can track motion but that their response is opposite to control flies under defined experimental conditions. In a fixation paradigm, which allows tethered flies to control the angular position of a visual stimulus, mutant flies’ responses were diametrically opposed to those seen in control flies. These data suggest that modest changes in the modularity of the fly visual system in the Dscam2 mutant can dramatically change the perception of specific visual cues and modify behavior.